Designing Mobile Phone Interfaces for Age Diversity in South Africa: “One-World” versus Diverse “Islands” - (:unkn) unknown (My University, 2013)
Designing for diversity is a laudable aim. How to achieve this, in the context of mobile phone usage by South African seniors, is a moot point. We considered this question from two possible perspectives: universal (one-world) versus focused design (designing for diverse “islands” of users). Each island would be characterised by a measure of relative homogeneity in terms of user interface needs. Our particular focus in this paper is age diversity. The universal approach attempts to deliver a design that can be all things to all people – meeting the needs of all users within one user interface. The islander approach delivers specific and different designs for islands within a diverse world. To determine which the best approach would be, in the South African context, we dispatched a team of student researchers to interview participants from an older generation, on a one-to-one basis. It was beneficial to deploy aspiring designers to carry out this research because we wanted to confront aspiring researchers with the differences between their own and other generations’ usage of, and attitudes towards, mobile phones. Our study found that there were indeed significant age-related differences in mobile phone usage. Our research delivered insights that led to a model of the factors impacting mobile phone usage of the senior generation as a series of filters between the user and their device. We conclude that the island approach is more suitable for age-specific design. This approach might well become less fitting as a more technologically experienced population ages, but at present there is a clear need for an age-sensitive mobile interface design.
Keywords: African Research